Liquidity Shortages and Monetary Policy - Gerhard Illing; Jin Cao (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
The paper models the interaction between risk taking in the financial sector and central bank policy. It shows that in the absence of central bank intervention, the incentive of financial intermediaries to free ride on liquidity in good states may result in excessively low liquidity in bad states. In the prevailing mixed-strategy equilibrium, depositors are worse off than if banks would coordinate on more liquid investment. It is shown that public provision of liquidity improves the allocation, even though it encourages more risk taking (less liquid investment) by private banks.
urn:nbn:de:bvb:19-epub-2008-6
Keywords: E5; G21; G28; 330; Liquidity Provision; Monetary Policy; Bank Runs; Liquidität; Geldpolitik; Finanzkrise; Geldpolitische Transmission; Geldnachfrage; Geldtheorie; Theorie